2018
DOI: 10.1680/jstbu.16.00137
|View full text |Cite
|
Sign up to set email alerts
|

Research on steel-plate–concrete walls with inclined studs under combined loads

Abstract: A numerical study was conducted to investigate the effect of the shape and spacing of developed inclined studs on the behaviour of steel-plate-concrete shear walls subject to combined loads of axial force, bending moment and shear. Finite-element analyses considering different shapes and stud spacings were carried out. The results showed that the compressive strength of the steel-plate-concrete walls was approximately three times higher than their tensile strength. Comparing the numerical analyses with designs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…A comparison of the experimental results with the predicted results based on Eurocode 4 indicated that different buckling curve can be adopted to yield efficient design for concrete-filled seamwelded rectangular hollow columns. The seventh paper (Lim and Yi, 2018) presents a numerical investigation on the behavior of steel-plate-concrete shear walls under combined loads. The effect of the shape and spacing on the proposed inclined studs was examined.…”
mentioning
confidence: 99%
“…A comparison of the experimental results with the predicted results based on Eurocode 4 indicated that different buckling curve can be adopted to yield efficient design for concrete-filled seamwelded rectangular hollow columns. The seventh paper (Lim and Yi, 2018) presents a numerical investigation on the behavior of steel-plate-concrete shear walls under combined loads. The effect of the shape and spacing on the proposed inclined studs was examined.…”
mentioning
confidence: 99%